Principles of Forming A Healthy Lifestyle Among Students Through Physical Education and Sports (Journal of Pedagogical Inventions and Practices, 2022)
In this article, the structure of human organs and the irfunctional maturity. Internal organs, nerves and movement, musculoskeletal system, control of body harmony and their functional activity